Green Innovation for Coastal Sustainability through Plastic Waste Recycling - Nitri Mirosea; Intihanah; Vina Olivia Pebrianti; Syaiah; Mutmainnah Mutmainnah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Plastic waste has become a major environmental challenge in the coastal areas of Kendari City due to increasing community activities and the widespread use of single-use plastics. This community service program aimed to improve public knowledge and awareness of circular economy-based plastic waste management while providing recycled products as educational media and waste management facilities. The program consisted of a preliminary survey, community outreach and education, production of recycled products, and distribution to partner institutions, including the Bungkutoko Village Office, Bungkutoko TPS3R, SD Negeri 89 Kendari, and the Faculty of Economics and Business, Halu Oleo University. Recycled products included trash bins made from wire frames and plastic bottles, flower pots from plastic bottles, and handicrafts from bottle caps. The program increased community knowledge and awareness of waste sorting and reuse, while strengthening community-based waste management facilities and supporting the implementation of circular economy principles in coastal areas.